Effect of Nd:YAG capsulotomy on the morphology of surviving Elschnig pearls. Issue 12 (18th September 2009) - Hirnschall, N; Neumayer, T; Georgopoulos, M; Findl, O
Abstract : Aim: To observe the short-term changes in morphology of Elschnig pearls induced by Nd:YAG capsulotomy. Setting: Department of Ophthalmology, Medical University of Vienna, Austria Method: Twenty eyes of 19 pseudophakic patients with regeneratory posterior capsule opacification (PCO) that were scheduled for YAG capsulotomy were included in this prospective study. High-resolution digital retroillumination images were taken 2 weeks, 1 week and shortly before and immediately, 1 week and 2 weeks after Nd:YAG capsulotomy. The series of images were analysed using a dedicated image analysing software (PearlTracer). Results: In total, 2431 Elschnig pearls were observed over the time-course of 4 weeks in this study. Of these, 535 pearls (30.6%) disappeared, and 503 pearls (27.6%) survived on the remaining capsule peripheral to the capsulotomy opening. The surviving pearls showed a significant decrease in size (20%) from immediately before to 10 min after capsulotomy. Within the first weeks after capsulotomy, there was a high number of newly appearing pearls, with 26% of all pearls being new between 1 and 2 weeks indicating high pearl turnover. Conclusion: Capsulotomy had an immediate impact on the morphology of PCO outside the capsulotomy opening, probably due to the direct mechanical impact of the laser shockwave.